Critical Discourse Analysis on Arvin's Criticism on Deddy Corbuzier's Youtube Channel - Al Faruq, Suhaib; Mahsun; Sirulhaq, Ahmad; Burhanuddin; Johan Mahyudi (LPPM Universitas Advent Indonesia, 2025)
Critical discourse studies as manifested are not just an analysis of people's social behavior as reflected through language. In relation to critical discourse studies, the language units that are the object of study are narrated as a reflection of social praxis, where linguistic units that are suspected of containing criticism can be used as material to reconstruct the intent or purpose of conveying criticism; whether criticism is aimed only at building humor between epistemic groups or is it more than just criticizing, meaning that criticism is used to fight against the domination of power. This research aims to describe the status of criticism in the principles of interpretation of critical discourse studies, especially with regard to global, local meaning and context models. The source of research data was obtained by transcribing criticism of subpoena video footage on Deddy Corbuzier's YouTube channel. The research used a qualitative descriptive approach, in which data was collected using a free-to-read, skillful listening method. The data is then analyzed by interpreting the context, semantic macrostructure, local and global meaning, relevance of the formal structure of discourse, and interpretation of the context model using the extralingual equivalent method. The results of the research show that the criticism made by comedians on Deddy Corbuzier's summons channel contains three strategic problems which are manifested by interpreting global, local meanings, as well as the discourse context model in the criticism.